Effect of short-term increase in occlusal vertical dimension on masticatory muscle electrical activities and pressure-to-pain threshold: A crossover clinical study - Ribeiro, Adriana Barbosa; Pita, Murillo Sucena; Ribeiro, Aline Barbosa; Garcia, Alício Rosalino [UNESP]; Junqueira Zuim, Paulo Renato [UNESP] (Elsevier, 2021)
Statement of problem: Increasing the occlusal vertical dimension (OVD) is a common procedure in clinical practice. However, few studies have assessed the short-term influence of an increased OVD on the masticatory muscles. Purpose: The purpose of this crossover clinical study was to investigate the effect of increased OVD on the electrical activity of masticatory muscles and the pressure-to-pain threshold (PPT) in asymptomatic participants. Material and methods: Twenty asymptomatic participants (22.7 ±2.39 years of age; 10 men, 10 women) were submitted to an increase in OVD by using interocclusal devices of different thicknesses (3- and 6-mm) for 24 hours. Masticatory muscle activity was assessed with electromyography (EMG), expressed in microvolts (μV), while the participants masticated 2 pieces of latex of different consistency (latex S and H) with and without the device. The PPT was measured with a digital algometer before and after the mastication. The results were assessed by using analysis of variance (ANOVA) and the Tukey honestly significant difference (HSD) test (α=.05). Results: The change of OVD did not significantly affect the electrical activity of the muscles. The latex of hard consistency (latex H) showed higher electrical activity values than the soft texture (latex S). For the working side anterior temporal muscle, a change in the PPT was detected on the day the 6-mm-device was inserted, but for the other muscles, device thickness and latex mastication did not change the PPT. Conclusions: For a short time, an increase in occlusal vertical dimension did not affect the electrical activity in the masticatory muscles or pressure-to-pain threshold in asymptomatic participants.